Democratic Participation in Early Childhood Education and Care - Serving the Best Interests of the Child - Evelyn Eriksen (Nordisk Barnehageforskning, 2018)
Abstract: The meaning of democratic participation in Early Childhood Education and Care (ECEC) remains vague and difficult to implement. Thus, the aim of this paper is to contribute to this gap of knowledge by shed light on the meaning of democratic participation in relation to the best interests of the child, by analysing General Comment No. 14 (2013). The research uses theories on democracy in ECEC to discuss the results (Biesta, 2014, 2015; Moss, 2007, 2011; Pettersvold, 2013; Einarsdottir, Purola, Johansson, Broström, & Emilson, 2015). The study investigates how key terms (rights, participation, unity/collective, equality, influence and responsibility) relate to democratic participation. Findings indicate that these terms are used to align with ideas about the “best interests of the child”. Furthermore, the study identified specific groups of children who can be in vulnerable situations and their explicit right to express their views and to influence decisions affecting them in ECEC institutions. I therefore argue that understanding democracy in ECEC must focus on inclusion of children who can be in vulnerable situations because this is in the best interests of the child.